eLIPS: Development and Validation of an Observational Tool for Examining Early Language in Play Settings - Duncan, Lynne G.; Gollek, Conny; Potter, Douglas D. (Frontiers in Psychology, 2020)
Intervention in the early years can help to mitigate the risks that early language and communication difficulties pose for later learning and well-being. Critical to this is the capacity of early years educators to evaluate language development accurately in the classroom in order to target individual support effectively. This article reports on the development and testing of the Early Language in Play Settings (eLIPS) tool, an observational measure of child language. An action research model was used in the design of the tool with the result that the methodology adopted was compatible with an early years child-centered approach. Observations of children in play settings were used to gather information about early language through subscales measuring social communication, receptive and expressive language. A series of preliminary trials with 3-to-5-year-olds, established that the eLIPS measures have concurrent validity with scores from a standardized language assessment, the Clinical Evaluation of Language Fundamentals-Preschool 2UK. Investigation of internal consistency showed reliability for use by researchers and early years educators together with inter-rater reliability across these groups. It was concluded that eLIPS has potential as a tool to assist early years educators in understanding individual patterns of language acquisition in a play-based environment and for framing team discussions about approaches to early language support.